Retinoic Acid Signaling: A New Piece in the Spoken Language Puzzle - van Rhijn, Jon-Ruben; Vernes, Sonja C. (Frontiers in Psychology, 2015)
Speech requires precise motor control and rapid sequencing of highly complex vocal musculature. Despite its complexity, most people produce spoken language effortlessly. This is due to activity in distributed neuronal circuitry including cortico-striato-thalamic loops that control speech–motor output. Understanding the neuro-genetic mechanisms involved in the correct development and function of these pathways will shed light on how humans can effortlessly and innately use spoken language and help to elucidate what goes wrong in speech-language disorders. FOXP2 was the first single gene identified to cause speech and language disorder. Individuals with FOXP2 mutations display a severe speech deficit that includes receptive and expressive language impairments. The neuro-molecular mechanisms controlled by FOXP2 will give insight into our capacity for speech–motor control, but are only beginning to be unraveled. Recently FOXP2 was found to regulate genes involved in retinoic acid (RA) signaling and to modify the cellular response to RA, a key regulator of brain development. Here we explore evidence that FOXP2 and RA function in overlapping pathways. We summate evidence at molecular, cellular, and behavioral levels that suggest an interplay between FOXP2 and RA that may be important for fine motor control and speech–motor output. We propose RA signaling is an exciting new angle from which to investigate how neuro-genetic mechanisms can contribute to the (spoken) language ready brain.